Insights into insect wing origin provided by functional analysis of vestigial in the red flour beetle, Tribolium castaneum - Clark-Hachtel, Courtney M. (National Academy of Sciences, 2013)
Despite accumulating efforts to unveil the origin of insect wings, it remains one of the principal mysteries in evolution. Currently, there are two prominent models regarding insect wing origin: one connecting the origin to the paranotal lobe and the other to the proximodorsal leg branch (exite). However, neither hypothesis has been able to surpass the other. To approach this conundrum, we focused our analysis on vestigial (vg), a critical wing gene initially identified in Drosophila. Our investigation in Tribolium (Coleoptera) has revealed that, despite the well-accepted view of vg as an essential wing gene, there are two groups of vg-dependent tissues in the “wingless” first thoracic segment (T1). We show that one of these tissues, the carinated margin, also depends on other factors essential for wing development (such as Wingless signal and apterous), and has nubbin enhancer activity. In addition, our homeotic mutant analysis shows that wing transformation in T1 originates from both the carinated margin and the other vg-dependent tissue, the pleural structures (trochantin and epimeron). Intriguingly, these two tissues may actually be homologous to the two proposed wing origins (paranotal lobes and exite bearing proximal leg segments). Therefore, our findings suggest that the vg-dependent tissues in T1 could be wing serial homologs present in a more ancestral state, thus providing compelling functional evidence for the dual origin of insect wings.